"Variation" in Approaches to Human Psyche: Exploring Al-Ghazālī's Influence on Freudian Psychoanalysis. Issue 1 (2nd January 2022) - Mobarak, Tanzia
ABSTRACT: This paper undertakes a comparative study of Imam Al-Ghazālī's and Sigmund Freud's conceptions of the self or personality and explores whether, Al-Ghazālī may have influenced Freudian psychoanalysis. An influential 11 th -century Persian scholar, Al-Ghazālī remains one of the most widely read Muslim scholars who wrote freely on topics ranging from jurisprudence, logic and ethics to theology and spirituality. A lesser-explored area of his oeuvre is his contribution to psychology, manifested expressively in his monumental Iḥyāʾ ʿulūm Al-Dīn ( The Revival of the Religious Sciences ). The early 20 th -century Austrian scholar Sigmund Freud, on the other hand, is revered as the founder of psychoanalysis – the theory and practice associated with the study of mental processes. The methodology adapted for this study is the Variation theory of comparative literature developed by Shunqing Cao. This is because Variation is especially suitable for conducting such cross-civilization comparative studies. Through this critical endeavor, the paper aims to investigate the possibility of cross-cultural influence and foreground the potential of a rarely applied non-Western theoretical framework.